Pelatihan Hidroponik Sebagai Upaya Peningkatan Keterampilan dan Ketahanan Pangan Siswa di Sekolah Indonesia Davao (SID) Filipina - Priyo Heru Adiwibowo; Ahmad Saepuddin; Akhmad Hafizh Ainur Rasyid; Aisyah Endah Palupi; Muhaji Muhaji; I Made Arsana; A Grummy Wailanduw; Indra Herlamba Siregar; Aris Ansori; Mochamad Arif Irfa’i; Hanna Zakiyya; Aris Purwanto (I-Com: Indonesian Community Journal, 2025)
Hydroponics training at the Indonesian School of Davao (SID) Philippines aims to improve students' skills in growing crops using soilless methods. Hydroponics is an effective solution for sustainable agriculture in countries with limited land. This training was carried out in three stages: pre-activity, implementation, and evaluation. The pre-activity stage identifies problems in implementing modern agricultural technology in schools. During implementation, students gain theoretical and practical understanding of hydroponic systems, including planting media selection, plant care, and nutrient management. Evaluation is carried out to assess the skills students acquire after training. Participants' response to the training reached 97%, reflecting high satisfaction and interest in the material presented. These findings confirm that hydroponic training can be an effective solution in preparing students to face the challenges of sustainable agriculture in the future. The results of the training show that students are able to manage hydroponic systems independently and understand the importance of environmentally friendly agriculture, as well as the skills needed to face agricultural challenges in the future.